Decorative Eggs - Manroe, Candace Ord (Magna Books, 1992)
Covers the history of the egg from traditional and symbolic applications to its role in the decorative arts, including chocolate eggs, Ukrainian pysanky, and jeweled Faberge eggs, and provides instructions for making decorative eggs at home
Keywords: Crafts & Hobbies; Nature Crafts